A cybernetic communication model for advertising - Miles, Chris J. (My University, 2007)
Taking as its starting point Barbara B. Stern's (1994) ‘A Revised Communication Model for Advertising’, the article argues for the application of first-order and second-order cybernetic principles to the construction of a more multidimensional and realistic model that is able to address well-documented tensions and problems in the advertising system and provide a fresh perspective on issues connected with interactive advertising and the creative component in advertising communication. The article culminates in a radical second-order cybernetic model of advertising communication that is founded upon the relationship between various observing frames and the stabilized eigenforms (constructions of the self and others produced by an observer) that are generated in the communication process. © 2007, Sage Publications. All rights reserved.
Keywords: advertising; communication; cybernetics; feedback; interactivity; theory